Role of Satisfaction with Health Care Services in Increasing Patient Loyalty: an Ambulatory Setting - Citra Restia Yusri; Marlianti Hidayat; Henni Djuhaeni (Althea Medical Journal, 2017)
Background: Health care providers must be able to provide services that can satisfy the patient. This encourages patient loyalty so that competitiveness can be preserved. This study aimed to examine the correlation of patients’ satisfaction to their loyalty towards health care facilities.Methods: An analytic cross-sectional study was conducted on 50 respondents from Anggrek Specialist Polyclinic at Dr. Hasan Sadikin General Hospital Bandung (ambulatory setting) who met the inclusion criteria during the period of September to October 2014. Questionnaires that had been validated and tested for reliability were used. Rank Spearman test was used to analyze the correlation between patient satisfaction and patient loyalty. This study used five dimensions of service quality to measure patient satisfaction, i.e. tangibles, reliability, responsiveness, assurance, and empathy.Results: The study showed that most (84%) patients felt unsatisfied and only 14% was loyal towards the health care services they received. Satisfaction and loyalty showed positive correlation with p=0.001 (p<0.05) and r=0.439, which showed a moderate correlation.  Conclusions: There is significant correlation between patient satisfaction and loyalty in Anggrek Specialist Polyclinic at Dr. Hasan Sadikin Hospital. This study can be an evaluative material for health care providers to encourage improvement of service quality as to increase patient satisfaction and loyalty.